Schools as a system to improve nutrition: A new statement for school-based food and nutrition interventions - Hunter, D.; Giyose, B.; PoloGalante, A.; Tartanac, Florence; Bundy, D.; Mitchell, Arlene; Moleah, T.; Friedrich, J.; Alderman, Harold; Drake, Lesley; Kupka, Roland; Marshall, Quinn; et al. (United Nations Systems Standing Committee on Nutrition, 2017)
This paper asserts that schools offer a unique platform from which to realize multiple benefits for children and their communities, while helping to achieve the SDGs. Furthermore, schools can exert influence beyond the student population, serving as a foundation for the involvement of teachers, parents and other community members. Intervention can catalyze community development, bring about social protection and economic empowerment, influence agricultural production systems to deliver diverse and nutritious foods, promote lifelong healthy-eating habits, and address basic health, hygiene, and sanitation issues that affect wellbeing. By providing a better health and living environment, schools have the potential to not only support education, but also underpin mainstream nutrition activities in communities and advance child development (Patton et al. 2016).